Girls who run the world : 31 CEOs who mean business - Kapp, Diana (Diana E.) (Delacorte Press, 2019)
Part biography, part business how-to, and fully empowering, this book is the perfect gift for future entrepreneurs...because you're never too young to dream BIG! -- amazon.com